Social safety nets for vulnerable and low income group: a case study of fishing communities in Malaysia / Abdul Rahim Anuar ... [et al.] - Anuar, Abdul Rahim; Ibrahim, Ahmad Zubir; Kamaruddin, Roslina; Hassan, Kalthum (2018)
Social safety nets can preserve and sustain fishermen livelihoods. The mechanisms for implementing the social security nets model for fishermen should be based on their sustainable livelihood index that comprised of livelihood assets, vulnerable context faced by them and resilient strategies of fishermen when faced with economic shocks. These index and indicators were obtained from the findings of this study involving the use of questionnaires distributed to 400 fishermen in Kedah related to the sustainability of their livelihoods. In the context of livelihood asset index, these fishermen attained the highest index for physical assets (0.65), followed by social (0.54), human (0.50), natural (0.42), and the lowest being finance (0.26). This is in line with their economic status, where most of them having low-income and are poor. They are also trapped in a vicious poverty cycle. Additionally, these fishermen are vulnerable to the rising prices of basic necessities at present by recording the highest index level of vulnerability, 3.12, compared to other threats. This is consistent and in line with the thrifty strategy adopted in their spending, with the highest resilient strategy score (3.60) compared to other strategies. In addition to financial assistance in the form of subsidies, the mechanism for implementing a social safety net model for these fishermen needs to pay attention to changes in values and attitudes to improve the value of self-efficacy. This capacity building will encourage them to increase productivity of their economic activity and thus attaining higher income and remove themselves from the poverty trap.